Interferons as Inducers of Apoptosis in Malignant Cells - Kotredes, Kevin P. (Mary Ann Liebert, Inc., 2013)
Discovered as antiviral cytokines, interferons (IFNs) are now also recognized for their capacity to inhibit the growth of malignant cells via activation of programmed cell death, better known as apoptosis. In this review, we will cover recent advances made in this field, as it pertains to the various proposed mechanisms of IFN-induced apoptosis and the characterization of IFN-responsive genes not previously known to have apoptotic function. Also mentioned here is a description of the activation and crosstalk of survival signaling pathways as a mode of IFN resistance that remains a persistent clinical adversary to overcome and the future of IFNs as antitumor agents.